A High-fidelity Tactile Hand Simulator as a Training Tool to Develop Competency in Percutaneous Pinning in Residents. (July 2018) - Wu, Ying Ying; Rajaraman, Mabaran; Guth, Jared; Salopek, Traci; Altman, Dan; Sangimino, Mark; Shimada, Kenji
Abstract : Introduction: We developed an economical three-dimensional printed and casted simulator of the hand for the training of percutaneous pinning. This simulator augments the traditional "See one, do one, teach one" training model. Methods: To evaluate the simulator, five expert orthopaedic surgeons were recruited to perform percutaneous pinning on the simulator and then to complete a questionnaire on its realism and expected usefulness. Evaluation was based on responses to multiple-choice questions and a Likert-type scale. Results: All subjects expressed that the tactile hand simulator is useful for residency training. They would recommend the simulator to their colleagues and indicated interest in testing future iterations. Subjects rated highly the realism of the material, the purchase of the pin, and the cortical–cancellous bone interface. Conclusion: The learning of tactile skills in addition to visual cues on a tactile simulator is expected to benefit residents. It provides a low-cost and low-risk environment outside the operating room for residents to hone their skills.